Software Agents, Agent Systems and Their Applications - Essaaidi, M; Ganzha, M; Paprzycki, M (Sage Publications Ltd, 2012)
Seen by many as the next revolution in software development for large, complex, distributed systems, agent systems represent one of the more exciting research areas in computer science. With the development of powerful personal devices, the vision of a personal agent seems increasingly appealing too. It can even be claimed that intelligent software agents will eventually become an essential part of Web 4.0. Software agents are finding their way into areas such as environmental security, climate change, seismic safety, epidemic prevention, detection and response, computer emergency response and human and societal dynamics. Because these are of direct interest to the NATO Science for Peace and Security Programme, a NATO Advanced Study Institute (ASI) dealing with software agents and their applications was held in Tangier, Morocco, in September 2010. This book presents the content of that ASI. This book is divided into three sections: Foundations, Applications, and Student Papers. Subjects covered include, among others, agent system modeling, system design and experimentation, sensor networks, disaster management, e-health and medical emergencies, management of UAVs. Agent systems security and the application of agents in network security are also addressed, and the final section includes student papers. The book has been designed to be usable as a textbook - for example, in a graduate course covering software agents, agent systems and their applications - but it will be of interest to everyone involved in related fields.